Landuse changes on the floodplain of River Maros since the XIX. century - Oroszi, Viktor György; Kiss, Tímea (JOURNAL OF LANDSCAPE ECOLOGY, 2006)
During our research we intended to determine the pre- and post-regulation environmental conditions of the Maros floodplain, since these factors are in a very strong relation with the type and amount of sedimentation. As the vegetation has an important role in determining the friction coefficient of the floodplain, it influences significantly the pattern and quantity of sediment accumulation. Besides, the evaluation of the vegetation cover also helps in the analysis of the palynological data gained from earlier cut-off meanders, since in a fluvial environment the dominance of the native vegetation is greatly modified by the presence of allochtonuous pollens, transported from greater distances during floods. The study site was covered by riparian forests and moors before the river regulation works (before the middle of the 19. century). In the 1950’s two-third of the territory was covered by arable lands and a quarter by planted forests. Nowadays 70% of it is covered by forests, the most of which is noble poplar plantation. During the second half of the century simple shaped patches characterized the territory, which were resembled in the changes of landscape metrics. During our continuity investigations we were aware of the consistency of the patches. Pits along the levee represented the highest diversity, where small and complex shaped patches of wetlands were combined with forests. The most consistent patches were the grasslands on the slope of the levee.
Keywords: River Maros; landscape metrics; landuse change; pollen analysis